Advances in therapies using mesenchymal stem cells and their exosomes for treatment of peripheral nerve injury: state of the art and future perspectives - Fatima Aldali; Chunchu Deng; Mingbo Nie; Hong Chen (Neural Regeneration Research)
“Peripheral nerve injury” refers to damage or trauma affecting nerves outside the brain and spinal cord. Peripheral nerve injury results in movements or sensation impairments, and represents a serious public health problem. Although severed peripheral nerves have been effectively joined and various therapies have been offered, recovery of sensory or motor functions remains limited, and efficacious therapies for complete repair of a nerve injury remain elusive. The emerging field of mesenchymal stem cells and their exosome-based therapies hold promise for enhancing nerve regeneration and function. Mesenchymal stem cells, as large living cells responsive to the environment, secrete various factors and exosomes. The latter are nano-sized extracellular vesicles containing bioactive molecules such as proteins, microRNA, and messenger RNA derived from parent mesenchymal stem cells. Exosomes have pivotal roles in cell-to-cell communication and nervous tissue function, offering solutions to changes associated with cell-based therapies. Despite ongoing investigations, mesenchymal stem cells and mesenchymal stem cell–derived exosome-based therapies are in the exploratory stage. A comprehensive review of the latest preclinical experiments and clinical trials is essential for deep understanding of therapeutic strategies and for facilitating clinical translation. This review initially explores current investigations of mesenchymal stem cells and mesenchymal stem cell–derived exosomes in peripheral nerve injury, exploring the underlying mechanisms. Subsequently, it provides an overview of the current status of mesenchymal stem cell and exosome-based therapies in clinical trials, followed by a comparative analysis of therapies utilizing mesenchymal stem cells and exosomes. Finally, the review addresses the limitations and challenges associated with use of mesenchymal stem cell–derived exosomes, offering potential solutions and guiding future directions.